The feasibility of health professional student delivered social visits for stroke survivors with loneliness - Burnett, Jason; Broussard, Jordan; Ciavarra, Bronson; Smitherman, Louisa; Li, Mary; Thames, Emma; Zachariah, Sharon; Kim, Grace; Pijnnaken, Rachel; Zeller, Hannah; Halphen, John; Savitz, Sean I.; et al. (Frontiers in Stroke, 2024)
Objectives: To examine the feasibility of a social phone call program to address social isolation and loneliness in stroke survivors. Materials and Methods: We paired 14 lonely communityliving stroke survivors with 14 health professional students for 6-weekly unstructured social phone calls. Feasibility data and measures of social isolation, loneliness and other psychosocial metrics were collected pre-and post-intervention. Students journaled following each unstructured call to capture the informal conversation and their sentiments. Results: Sixty-two percent of the targeted sample was interested. Fourteen eligible and interested participants were enrolled. The 13 (93%) participants completing all calls and surveys were an average of 57 years old, 85% female, and 77% non-Hispanic white. At baseline, participants were highly lonely and moderately depressed.Participants disclosed physical and emotional challenges, previous valued employment, and enjoyment from the calls. Students reported enjoying the connections, learning about the struggles of aging-in-place after stroke, and valuing compassionate care for the stroke population.Conclusions: Knowledge gaps remain regarding effective social support interventions to provide continuity of care directed at managing social disconnection after stroke. A health professional student-delivered social phone call intervention with stroke survivors appears to be a feasible, in part, and encouraging approach for addressing social isolation and loneliness. Future trials require re-evaluation of eligibility criteria and strategies to boost enrollment before efficacy testing is conducted in a larger trial.